A dedicated scholarly research program in an adult and pediatric neurology residency program. (4th April 2017) - Robbins, Matthew S.; Haut, Sheryl R.; Lipton, Richard B.; Milstein, Mark J.; Ocava, Lenore C.; Ballaban-Gil, Karen; Moshé, Solomon L.; Mehler, Mark F.
Abstract : Objective: To describe and assess the effectiveness of a formal scholarly activity program for a highly integrated adult and pediatric neurology residency program. Methods: Starting in 2011, all graduating residents were required to complete at least one form of scholarly activity broadly defined to include peer-reviewed publications or presentations at scientific meetings of formally mentored projects. The scholarly activity program was administered by the associate residency training director and included an expanded journal club, guided mentorship, a required grand rounds platform presentation, and annual awards for the most scholarly and seminal research findings. We compared scholarly output and mentorship for residents graduating within a 5-year period following program initiation (2011–2015) and during the preceding 5-year preprogram baseline period (2005–2009). Results: Participation in scholarship increased from the preprogram baseline (24 of 53 graduating residents, 45.3%) to the postprogram period (47 of 57 graduating residents, 82.1%, p < 0.0001). Total scholarly output more than doubled from 49 activities preprogram (0.92/resident) to 139 postprogram (2.44/resident, p = 0.0002). The proportions of resident participation increased for case reports (20.8% vs 66.7%, p < 0.0001) and clinical research (17.0% vs 38.6%, p = 0.012), but were similar for laboratory research and topical reviews. The mean activities per resident increased for published abstracts (0.15 ± 0.41 to 1.26 ± 1.41, p < 0.0001), manuscripts (0.75 ± 1.37 to 1.00 ± 1.40, p = 0.36), and book chapters (0.02 ± 0.14 to 0.18 ± 0.60, p = 0.07). Rates of resident participation as first authors increased from 30.2% to 71.9% ( p < 0.0001). The number of individual faculty mentors increased from 36 (preprogram) to 44 (postprogram). Conclusions: Our multifaceted program, designed to enhance resident and faculty engagement in scholarship, was associated with increased academic output and an expanded mentorship pool. The program was particularly effective at encouraging presentations at scientific meetings. Longitudinal analysis will determine whether such a program portfolio inspires an increase in academic careers involving neuroscience-oriented research.